URGENSI ADAB DALAM MENUNTUT ILMU: PEMIKIRAN NAQUIB AL-ATTAS - Andika Apriansyah; Abdur Razzaq; Alimron (LPPM Universitas Cipta Mandiri, 2024)
Seeking knowledge is something that should be done by all levels of society. Both world knowledge, where a person needs this knowledge for survival, and religious knowledge which is of course the main foundation for all aspects of life. Manners, morals, ethics are of course things that are often put forward by everyone, and you can see how someone currently assesses each person's personality, by looking at their manners. From this research, the aim is to find out the urgency of adab in seeking knowledge, by looking at Naquib al-Attas' thoughts on this matter. This research is library research, using descriptive qualitative research methods. The urgency of adab in seeking knowledge is very important, because if existing knowledge is damaged, this is caused by damage to the etiquette and morals of each party, and causes the spread of ignorance.